Peran Penempatan Kerja dalam Memoderasi Pengaruh Kompetensi dan Kepribadian terhadap Kinerja Karyawan Perusahaan Umum Daerah Air Minum di Wilayah Priangan Timur - Agus Teguh Suryaman; Kartawan, Kartawan; Yusuf Abdullah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The aim of the study was to determine and analyze the role of job placement in moderating the effect of competence and personality on employee performance at Perusahaan Umum Daerah Air Minum in the Priangan Timur Region. The method used in the study was a survey with a descriptive quantitative approach. The sample size in the study was 226 karyawants, selected through cluster sampling. Data analysis used Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings with moderation effects showed that competence, personality, and job placement had a positive and significant effect on employee performance at Perusahaan Umum Daerah Air Minum in the Priangan Timur Region. Job placement strengthened the effect of competence and personality on employee performance at Perusahaan Umum Daerah Air Minum in the Priangan Timur Region. The implication of this study showed that improving employee performance Perusahaan Umum Daerah Air Minum in the Priangan Timur area could be achieved through integrated management of competence, personality, and job placement.